Robust High-Gain Observers Based Liquid Levels and Leakage Flow Rate Estimation - Feten Smida; Salim Hadj Saïd; Faouzi M’sahli (Journal of Control Science and Engineering)
The paper aims to solve the problem of liquid level and leakage flow rate estimations for a state coupled four-tank process, that is why an UIO is developed to simultaneously estimate the unmeasured state variables and the perturbations considered as unknown inputs. We have proposed a state repartition that allows putting the model of the quadruple tank system to the canonical form for which the design of the observer is more easier. The observation scheme that uses a combination of high-gain observers and sliding mode observers allows improving robustness in the state estimation quality and a perfect reconstruction of the disturbance waveforms.